4-Thiazolidinone-based derivatives do not affect differentiation of mouse embryo fibroblasts (3T3-L1 cell line) into adipocytes. (25th August 2021) - Szychowski, Konrad A.; Skóra, Bartosz; Kryshchyshyn-Dylevych, Anna; Kaminskyy, Danylo; Tobiasz, Jakub; Lesyk, Roman B.; Gmiński, Jan
Abstract: Nowadays, diabetes mellitus type 2 (T2DM) is a serious problem in western European societies and in the United States. Thiazolidinediones (TZDs) are a broad group of compounds used to decrease insulin resistance in TDM2. To date, it has been believed that TZDs act mainly through activation of peroxisome proliferator-activated receptor gamma (PPARγ). The PPARγ receptor is important in differentiation of preadipocytes into mature adipocytes. Therefore, given the potential of structurally related thiopyrano[2, 3- d ]thiazoles Les-2194 and Les-3377 and 4-thiazolidinone derivative Les-3640 to interact with the PPARγ receptor, the aim of the present study was to evaluate the impact of the 4-thiazolidinone-based derivatives mentioned above on the process of 3T3-L1 cell line differentiation into adipocytes. In the first part of our study, we prove that Les-2194, Les-3377, and Les-3640 are cytotoxic to 3T3-L1 cells. In the next stage, we determine that Les-2194, Les-3377, and Les-3640 stimulate lipid accumulation (using the ORO staining method) and induce specific gene expression ( Dlk1, Fabp4, Vegfa, Pai-1, Resistin, Adiponectin, and Pparγ ). Our data show that rosiglitazone, pioglitazone, Les-2194, and Les-3640 at a concentration of 2 μM do not affect 3T3-L1 cell viability and do not activate the apoptotic process. Only Les-3377 decreased the number and metabolism of the cells. Although all the studied compounds influenced the expression of Dlk1, Fabp4, Vegfa, Pai-1, Resistin, Adiponectin, and Pparγ genes, none of them caused gene expression similar to that induced by rosiglitazone or pioglitazone. The ORO staining showed that rosiglitazone and pioglitazone induced lipid accumulation in the 3T3-L1 cell line, which is a marker of mature adipocytes. Only rosiglitazone increased Pparγ protein expression after 14 days of differentiation. Graphical abstract: Image 1 Highlights: Rosiglitazone, pioglitazone, Les-2194, and Les-3640 at a concentration of 2 μM do not affect 3T3-L1 cell viability. Les-3377 decreased the number and metabolism of cells and the expression of Pparγ, Resistin, Vegfa, and Fabp4 mRNAs. Only rosiglitazone and pioglitazone induced lipid accumulation in the 3T3-L1 cell line.